2011
DOI: 10.9790/3013-01101521
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic and Anti-inflammatory Activity of Roxithromycin and Erythromycin, Alone and in Combination with Ibuprofen: An Animal Study

Abstract: Background: Several in-vitro, animal and clinical studies have reported anti-inflammatory activity of macrolides. Antiinflammatory properties of macrolides form the basis for their experimental use in airway inflammatory and infective conditions like asthma Materials and Method: After animal ethics committee approval, the anti-inflammatory and analgesic potentials of erythromycin (40 mg/kg) and roxithromycin (20 mg/kg) were evaluated in carrageenan-induced rat paw edema model and rat tail flick model respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
(16 reference statements)
1
4
0
Order By: Relevance
“…Tilmicosin phosphate possessed central and peripheral analgesic activities at both doses (20-40 mg/kg, orally). These results were come in agreement with [38] they found that both roxithromycin and erythromycin had ant nociceptive effect.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Tilmicosin phosphate possessed central and peripheral analgesic activities at both doses (20-40 mg/kg, orally). These results were come in agreement with [38] they found that both roxithromycin and erythromycin had ant nociceptive effect.…”
Section: Discussionsupporting
confidence: 92%
“…The pain is induced due to liberation of endogenous substances as well as other pain mediators such as arachodonic acid via cyclooxygenase and prostaglandin biosynthesis especially PGE2 and PGF2α, which then stimulate the pain nerve endings [39,40] Tilmicosin phosphate signi icantly (p<0.05) inhibited acetic acid-induced writhes in mice. The inhibition in the pain might attributed to inhibition of pain mediators PGE2 which achieved by all macrolides [41] all macrolides via inhibition of hyperalgesic mediators such as PGE2¸ which are predominantly involved in peripheral pain [38].…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory properties of macrolides form the basis for their experimental use in bronchial asthma and air way inflammatory and infective conditions (Maselli et al, 2011;Vaz et al, 2011). Since Meloxicam is known inhibitor of cox-2, the combination of two anti-inflammatory drug acting via different mechanisms should have caused an increased effect also as seen in Khobragade et al (2011) study. This may be explained by the similarity in final targets in the inflammatory pathway at which macrolides and NSAIDS appear to act.…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies, such as Ianaro et al, 9 Prathima et al, 11 Khobragade et al, 14 Scaglione and Rossoni, 27 and Agen et al, 28 have also shown that macrolide antibiotics have anti-inflammatory activity using various animal models of inflammation. Our results correlate with the findings in above studies.…”
Section: Discussionmentioning
confidence: 99%
“…The most probable mechanisms of acute anti-inflammatory activity of macrolide antibiotics could be due to the inhibition of synthesis of prostaglandins, serotonin, histamine and other inflammatory mediators. 9,14,27 Insignificant chronic anti-inflammatory activity of macrolides could be due to that, they do not inhibit fibroblast proliferation and synthesis of collagen in chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%